Phytochemical characterization, antimicrobial activity and reducing potential of seed oil, latex, machine oil and presscake of Jatropha curcas - Sharma, Amit Kumar; Gangwar, Mayank; Kumar, Dharmendra; Nath, Gopal; Kumar Sinha, Akhoury Sudhir; Tripathi, Yamini Bhushan (Avicenna journal of phytomedicine, 2016)
This study aims to evaluate the antimicrobial activity, phytochemical studies and thin layer chromatography analysis of machine oil, hexane extract of seed oil and methanol extract of presscake & latex of Jatropha curcas Linn (family Euphorbiaceae). J. curcas extracts were subjected to preliminary qualitative phytochemical screening to detect the major phytochemicals followed by its reducing power and content of phenol and flavonoids in different fractions. Thin layer chromatography was also performed using different solvent systems for the analysis of a number of constituents in the plant extracts. Antimicrobial activity was evaluated by the disc diffusion method, while the minimum inhibitory concentration, minimum bactericidal concentration and minimum fungicidal concentration were calculated by micro dilution method. The methanolic fraction of latex and cake exhibited marked antifungal and antibacterial activities against Gram-positive and Gram-negative bacteria. Phytochemical analysis revealed the presence of alkaloids, saponins, tannins, terpenoids, steroids, glycosides, phenols and flavonoids. Reducing power showed dose dependent increase in concentration compared to standard Quercetin. Furthermore, this study recommended the isolation and separation of bioactive compounds responsible for the antibacterial activity which would be done by using different chromatographic methods such as high-performance liquid chromatography (HPLC), GC-MS etc. The results of the above study suggest that all parts of the plants possess potent antibacterial activity. Hence, it is important to isolate the active principles for further testing of antimicrobial and other biological efficacy.